Evaluation of central pancreatectomy and pancreatic enucleation as pancreatic resections – A comparison. (October 2015) - Wolk, Steffen; Distler, Marius; Kersting, Stephan; Weitz, Jürgen; Saeger, Hans-Detlev; Grützmann, Robert
Abstract: Introduction: For minor pancreatic resection such as enucleation (PE) and central pancreatectomy (CP) comparative data are rare. These techniques provide parenchyma-sparing alternatives to major resections (e.g. pancreaticoduodenectomy) for neuroendocrine tumors, cystic tumors or metastases. This study retrospectively compares the morbidity and mortality of both techniques, with special regard to the formation of postoperative pancreatic fistulas (POPF). Methods: Between December 1996 and November 2013 the postoperative events and clinical outcomes of 17 patients after pancreatic enucleation and 26 patients after central pancreatectomy were retrospectively analyzed from a prospectively collected database. Results: Perioperative mortality was 0% in both groups. There was no significant difference in the overall peri-operative morbidity (CP 80.8% vs. PE 82.4%). The major cause of the high morbidity was the formation of a POPF with 26.9% of the patients after CP and 35.3% after PE. Univariate analysis showed a BMI over 30 kg/m 2 in the CP group to be an independent risk factor. Additional minor complications, e.g. urinary tract infection, pleural effusion, etc. furthermore contributed to the perioperative morbidity. Conclusion: PE and central CP are feasible techniques for selected patients, but the indications are limited. Morbidity after these resections is high with the major cause being the development of a POPF. Highlights: Pancreatic enucleation and central pancreatectomy are feasible techniques for selected patients. Main cause of morbidity is formation of pancreatic fistula. The fistula rate is comparable to major pancreatic resections or distal pancreatectomy.